Strategic Development Directions for Pond LUSI as a Dark Tourism Destination Based on Emotional Motives - Lomboan, Hizkia; Sari, Kartika Eka; Rachmawati, Turningtyas Ayu (Journal of Regional and Rural Studies, 2025)
Dark tourism destinations arising from disaster contexts face complex challenges related to emotional sensitivity, ethical representation, and sustainable destination development. In the case of Pond LUSI, tourism development must carefully balance visitors' emotional motivations, the trauma experienced, collective memory, and the social healing of affected local communities. This study aims to develop an appropriate and contextually sensitive development framework for the dark tourism destination Pond LUSI by examining tourism development models through the lens of tourists' emotional motivations. The study adopted a literature review based on qualitative content analysis, analyzing 20 peer-reviewed journal articles using NVivo 12 to identify dominant thematic patterns linking emotional motivations and tourism development approaches. The findings suggest that Community-Based Tourism (CBT) is the most suitable development model for Pond LUSI, as community-related concepts are more prominently featured in the literature than sustainability or growth-oriented approaches. The analysis highlights five key development directions: collaborative governance involving multiple stakeholders, the creation of reflective and educational spaces, capacity building for community-based guides, cultural and creative expression based on local experiences, and post-visit activities that deepen emotional engagement. These findings suggest that emotionally focused dark tourism destinations like Pond LUSI should be developed through community-centered strategies that respect local trauma, strengthen social healing, and provide meaningful and reflective experiences for visitors..